Utilization of Kelakai Wetland Plants (Stennochlaena palutris) and Different Doses of Probiotics in Feed Formulations on the Growth of Climbing Perch (Anabas testudineus Bloch) - Fatmawati; Noor Arida Fauzana; Aminah (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of the study was to test the provision of feed made from kelakai with the best probiotic dose for the growth of climbing perch. It is expected that the feed formulation made from kelakai in the form of pellets will increase its growth by administering probiotics. The research method used a completely randomized design (CRD) with 4 treatments and 3 replications, rearing for 30 days in an aquarium. Treatment A: feeding pellets with 20% kelakai flour and 0% probiotics, treatment B: feeding pellets with 20% kelakai flour and 5% probiotics treatment C: feeding pellets with 20% kelakai flour and 10% probiotics, treatment D: giving pelleted feed with 20% kelakai flour and 15% probiotics. The results showed that all treatments were not significantly different, the highest relative length growth was in treatment C (20% kelakai flour; 10% probiotics), the highest relative weight growth of climbing perch was in D treatment (20% kelakai; 15% probiotics), survival 100 % in all treatments. Water quality is within a range that supports the growth and survival of climbing perch.